Computational fluid dynamics methodology for characterisation of leading edge erosion in whirling arm test rigs. (May 2019) - Herring, R; Dyer, K; MacLeod, A; Ward, C
Abstract: Blade leading edge erosion has developed into a significant issue for the offshore wind industry. Protection solutions, including polymer coatings and tapes, are often applied to increase the blade lifetime. Experimental evaluation of protection systems is typically conducted in whirling arm rain erosion test rigs. Currently, there is no thoroughly validated method to relate the test results to real-world erosion performance. Furthermore, the design of rigs is not sufficiently limited to enable comparison of results between different rigs. Industry guideline, DNV-GL-RP-0171, provides a comparison method to address this issue. This paper describes the development of a droplet particle tracking Computational Fluid Dynamics methodology for rain erosion test rigs, which models the impact strike characteristics of a droplet, the number of impacts and the effect of rig aerodynamics. The methodology was applied to two rigs with different aerodynamics. Rain erosion tests were conducted in the rigs on identical coating and aluminium samples. The results were compared against predicted number of impacts from the DNV-GL guideline. Contradictory results were found, concluding that the guideline does not provide an accurate comparison between all test rigs, as it does not account for rigs where large aerodynamic effects cause droplet concentrations or droplet break-up.